Corpus Analysis of the Language Around Sustainable Fashion - Romanchuk Viktoriia (My University, 2023)
The topicality of the research is stipulated by the role played by numerous neologisms that have sprung into use in the English language as a result of the rise of sustainable fashion over the last couple of years as well as by the absence of in-depth linguistic analysis of the discourse in the field within the framework of Lexicology, Sociolinguistic Studies, Semiotics, Word Formation, and Stylistics. The aim of the present study is to examine the language utilized within the semantic field of sustainable fashion in order to explore 1. new developments in language on social media, 2. use of manipulative linguistic techniques, and 3. effective language practices to elevate one’s brand, using the inventory of Sociolinguistics. The objective set foresees fulfilling of the following objectives: identify linguistic theories that can be used to analyze language on the topic of sustainable fashion; pinpoint the most common language manipulation strategies used in online advertisements of sustainable fashion; study the Morphology, Syntax, Semantics, Stylistics, and Pragmatics of the language relating to sustainable fashion; examine how speakers use language around sustainable fashion in context to convey intended meaning, including social and cultural factors that influence communication. The subject of this study is the language employed in relation to sustainable fashion used by brands as well as consumers. The object of this research is lexical, stylistic, morphological, semantic, syntactical, pragmatic features and manipulative strategies used in the discourse around sustainable fashion. Methods used. Quantitative data analysis in the form of a corpus-based analysis, which allowed for the identification of metrics such as frequency of usage; qualitative data analysis in the form of discourse analysis which revealed more information about factors like word formation, cohesion, syntax, new coinages, morphology, stylistic devices, complexity of the terminology, and use of imagery. Critical discourse analysis was the predominant type of discourse analysis used. It allowed to examine the language in relation to its social setting. Other research methods included the triangulation methodology and the Interview. The novelty of the topic lies in the intersection of two different fields - sustainability and language analysis. By combining these two fields, the study can shed light on how the language is used to frame the discourse around sustainable fashion, what kind of narratives are being constructed, and how they shape our understanding of sustainable fashion. The analysis also helps understand the complexities involved in promoting sustainable fashion practices. The practical significance of the findings is determined by their ability to be used in Practical English courses as well as theoretical and practical courses in Lexicology, Discourse Analysis, Communication Studies, Semantics, and Sociolinguistics. Additionally, the study offers insights into how fashion brands utilize web-based communications to convey brand personality, manipulate customers with the help of verbal and non-verbal means or to generate more interest in the brand. It also provides a helpful methodology that fashion businesses can adopt to make sure they are effectively communicating the intended brand personality, their sustainability goals and accomplishments. The paper consists of an introduction that highlights the relevance, object, subject, aim and objectives, actual material of the study, reveals its scientific novelty and relevance, theoretical and practical significance. The first chapter reveals the entire theoretical and methodological foundation for this research. The second chapter is a corpus-based analysis of the language around sustainable fashion in online communication and well as the language used by alleged sustainable UK brands. Finally, the third chapter is the linguistic analysis of Ukrainian sustainable fashion. The conclusions set out the main theoretical and practical results proposed in the paper and determined the prospects for further scientific research. There is also a list of references, list of illustrative material, appendices, and a summary at the end.
Keywords: corpus analysis; cognitive linguistics